The Influence of Jumping Training with Ball Obstacles on the Ability to Squat Style Long Jump in Class XI Students of SMA/SMK in Banyuasin - Wardhana, Wisnu; Rahman, Andi; Imansyah, Farizal (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the Effect of Exercise Jumping with a Ball Obstacle Against Squatting Style Long Jump Ability in Class XI Students SMA/SMK In Banyuasin. This research was conducted on some class XI students in Banyuasin Regency. This research is an experimental method with a Quasi-Experimental design in the form of One Group Pretest Posttest Design. The sample used is 20 people. Based on the results of the study, the average results of the squat-style long jump obtained in the pre-test Experimental group is 2.28 m and pre-test implementation The control group is 2.27 m, and the average result of the squat-style long jump in the post-test of the Experiment Group is 2.90 m and the implementation of the control group post-test is 2.30 m. Based on the results of the statistical calculations of the data above, the value of t-count = 13.33 is obtained and t-table = 1.7 29, so t-count = 13.33 > t-table = 1.729, then the hypothesis that reads, The Effect of Training Jumping With a Ball Obstacle Against Squatting Style Long Jump Ability in Class XI Students SMA/SMK In Banyuasin. Research is acceptable.